6‐Methylquinazolin‐4(3H)‐one Based Compounds as BRD9 Epigenetic Reader Binders: A Rational Combination of in silico Studies and Chemical Synthesis. Issue 35 (15th September 2022) - Colarusso, Ester; Gazzillo, Erica; Boccia, Eleonora; Giordano, Assunta; Chini, Maria Giovanna; Bifulco, Giuseppe; Lauro, Gianluigi
Abstract: 6‐methylquinazolin‐4(3 H )‐one‐based compounds were here identified and synthesized as novel binders of bromodomain‐containing protein 9 (BRD9) epigenetic reader. Accounting a fast and efficient synthetic route aimed to easily obtain differently 2‐ and 8‐disubstituted 6‐methylquinazolin‐4(3 H )‐one derivatives, a virtual library of synthesizable items was built and submitted to molecular docking experiments. Based on two 3D structure‐based pharmacophore models recently developed by us on BRD9, 16 compounds were selected and synthesized, using mild conditions with good yields in relatively short reaction times. Among them, 14, 16, 18, 22, and 26 emerged as the most potent compounds of these series, able to bind BRD9 at the low micromolar range of concentrations. These molecules also showed a promising selective behavior when tested against BRD4 bromodomain. These results highlighted the quinazolin‐4(3 H )‐one chemical core as a valuable scaffold for developing promising BRD9 binders. Abstract : Five 6‐methylquinazolin‐4(3 H )‐one based compounds were here selected, efficiently synthesized, and identified as new BRD9 binders. These compounds selectively bind BRD9 epigenetic reader in the low micromolar range.